Fool's gold why the Internet is no substitute for a library - Herring, Mark Y. 1952- (Jefferson, N.C. McFarland, 2007)
"This work skeptically explores the notion that the Internet will soon obviate any need for traditional print-based academic libraries, and makes a case for the library's staying power in the face of technological advancements"--Provided by publisher
Includes bibliographical references (p. 167-187) and index.
Keywords: Computer network resources -- Evaluation; Web sites -- Evaluation; Libraries and the Internet; Libraries and electronic publishing; Libraries -- Forecasting; Electronic books -- Forecasting